Analysis of the Influnce Service Quality, Promotion, and Location on Customer Satisfaction at Madira Skin & Beauty Care Mojokerep - Kistantia , Yunika Aldiaz Putri; Samari, Samari (Universitas Nusantara PGRI Kediri, 2025)
Research aim : The aim of this research is to examine the effect of both partially and simultaneously the quality of service, promotion and location at customer satisfaction. Design/Methode/Approach : The approach is quantitative using observation and questionnaire research methods. This research has an infinite population with sampling using nonprobability sampling method and using the technique used is purposive sampling with a total sample of 40 respondents. Research Finding : The results of this research indicate an influence that is significant either partially or simultaneously on the variables of service quality, promotion and location on customer satisfaction. Theoretical contribution/Originality : There are not many research on beauty clinic marketing because research often focuses on the retail or hospitality sector. Practitionel/Policy implication : This research requires Madira Skin & Beauty Care Mojokerep to improve service quality, optimize promotion by utilizing social media and ensure that it has a convenient location and can be easily accessed by customers. With this, customer satisfaction can be significantly increased while strengthening the competitiveness of beauty industry clinics. Research limitation : Limitations in this research are the difficulty in obtaining information or meeting directly with the owner of this beauty clinic due to having to manage three clinic branches and a busy schedule out of town.